Bottom‐up Construction of π‐Extended Arenes by a Palladium‐Catalyzed Annulative Dimerization of o‐Iodobiaryl Compounds. Issue 29 (3rd May 2018) - Zhu, Chendan; Wang, Di; Wang, Dingyi; Zhao, Yue; Sun, Wei‐Yin; Shi, Zhuangzhi
Abstract: A straightforward method was developed for construction of aromatic compounds with a triphenylene core. The method involves Pd‐catalyzed annulative dimerization of o ‐iodobiaryl compounds by double C−I and C−H bond cleavage steps. Simple reaction conditions are needed, requiring neither a ligand nor an oxidant, and the reaction tolerates a wide range of coupling partners without compromising efficiency or scalability. Significantly, the tetrachloro‐substituted synthon, 1, 6, 11‐trichloro‐4‐(4‐chlorophenyl)triphenylene, can be generated and used to prepare a series of fully fused, small graphene nanoribbons by a late‐stage arylation with arylboronic acids and a subsequent Scholl reaction. The synthetic strategy enables bottom‐up access to extended π‐systems in a controlled manner. Abstract : Bottoms up ! A palladium‐catalyzed system for annulative dimerization of o ‐iodobiaryl species enables C−H activation and construction of various aromatics with triphenylene cores. A chloro‐substituted synthon can be generated and used to prepare a series of fully fused, small graphene nanoribbons by late‐stage arylation and a subsequent Scholl reaction.